Low Fibrinogen Is Associated with Increased Bleeding-Related Re-exploration after Cardiac Surgery - Essa, Yasin; Zeynalov, Natig; Sandhaus, Tim; Hofmann, Michael; Lehmann, Thomas; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon, 2018)
Background Re-exploration after cardiac surgery remains a relatively frequent complication associated with adverse effects on outcome. We aimed to identify risk factors for re-exploration.Methods We retrospectively reviewed 2,403 patients having undergone cardiac surgical procedure between January 2013 and December 2014. Re-exploration was required in 114 patients (4.7%). Patients with oral anticoagulation, infective endocarditis, or a clearly identified bleeding source were excluded. Therefore, 42 patients remained for analysis. A matched cohort was selected for age, sex, ejection fraction, creatinine, and procedure out of the non–re-explored patients.Results Demographic data were similar in both groups, except for a higher prevalence of diabetes (45 vs. 21%; p = 0.036) in the non–re-explored patients. Surgery was elective in two-thirds and preoperative plasma fibrinogen concentration was lower in patients requiring re-exploration (2.8 ± 0.9 vs. 3.6 ± 0.9 g/L; p = 0.002). During the initial operation, re-explored patients received more packed red blood cells (1.5 ± 3 vs. 0 ± 1 units; p < 0.001), Postoperatively, re-explored patients had higher lactate levels (1.7 ± 1.4 vs. 1.3 ± 0.6 mmol/L, p = 0.044), more chest tube drainage (1,245 ± 948 vs. 685 ± 413 mL; p < 0.001), higher hospital mortality (19 vs. 7%; p = 0.19), and longer intensive care unit (ICU) stays (8 ± 8 vs. 4 ± 7 days; p = 0.010). In addition, more fibrinogen was administrated during the initial surgery. Plasma fibrinogen concentration upon arrival at the ICU was lower in patients requiring re-exploration (2 ± 0.6 vs. 2.7 ± 0.7 g; p < 0.001). Multivariable linear regression analysis identified fibrinogen upon arrival at the ICU as an independent predictor of postoperative bleeding.Conclusion Cardiac surgery patients with low perioperative plasma fibrinogen concentration appear to be more susceptible to bleeding and re-exploration. Re-exploration in this group of patients is associated with increased morbidity and mortality.
Keywords: fibrinogen; tamponade; bleeding; cardiac surgery